Metabolic cataract in an 8-year-old diabetic boy - Al-Agha, Abdulmoein; Ocheltree, Ali; Rashad, Reem; Abdelsalam, Ihab (The Turkish Journal of Pediatrics, 2012)
Cataracts are uncommon among children with insulin-dependent diabetes mellitus (IDDM); nonetheless, they could result in significant morbidity and a decrease in the life quality of these children. Duration of diabetes and metabolic control over the disease are important contributing factors in the development and advancement of cataract among diabetic pediatric patients. Ophthalmological examination at the time of IDDM diagnosis is recommended. Furthermore, persistent poor diabetic control and/or blurred vision in IDDM pediatric patients warrant prompt ophthalmological evaluation. We present the case of an 8-year-old with poorly controlled IDDM, who presented with bilateral cataract 27 months after his diagnosis with IDDM. We believe that such a presentation is rare; thus, increasing awareness of this particular diabetic complication is imperative.